Reconstruction of the Immigration Authority in Legal Protection of Indonesian Citizens Abroad - Lucky Agung Binarto; Made Warka; Slamet Suhartono; Otto Yudianto (Technium Social Sciences Journal, 2021)
This study uses normative research. Globalization is a reality that cannot be avoided, having an impact on increasing the mobility of the world’s population from one country to another. The mobility of the population is based on the various interests and goals that are different from each person, such as reasons for business, tourism, education, work and various other interests. Immigration as an institution whose authority, duties and functions are related to exit permits or the entry and exit of Indonesian citizens, as well as foreign citizens, should be given the authority to participate in helping carry out the duties of legal protection for Indonesian citizens abroad. With the addition of this one authority, the Immigration authority which originally had only 4 powers, namely the authority to provide public services, the authority to carry out the security function, the authority to carry out the function of law enforcement, and the authority to facilitate economic development, then one more authority to carry out the function of legal protection.